The Natural History and Treatment Outcomes of Perineural Spread of Malignancy within the Head and Neck - Warren, Timothy A.; Nagle, Christina M.; Bowman, James; Panizza, Benedict J. (Journal of Neurological Surgery Part B: Skull Base, 2016)
Understanding the natural history of diseases enables the clinician to better diagnose and treat their patients. Perineural spread of head and neck cancers are poorly understood and often diagnosis is delayed resulting in poorer outcomes and more debilitating treatments. This article reviews a large personal series of head and neck malignancy presenting with perineural spread along almost exclusively the trigeminal and/or facial nerves. A detailed analysis of squamous cell carcinoma of cutaneous origin is presented including an analysis of likely primaries, which most often have occurred months to years prior. The importance of early detection is reinforced by the highly significant (p < 0.0001) differences in disease specific survival, which occur, depending on how far along a cranial nerve the disease has been allowed to spread.
Keywords: perineural invasion; head and neck; skin cancer; squamous cell carcinoma; skull base surgery; perineural spread